Adsorption of copper using modified and unmodified sugarcane bagasse - Salihi, I.U. (Research India Publications, 2015)
This study compares the adsorption capacity of sugarcane bagasse and microwave incinerated sugarcane bagasse ash (MISCBA) for the adsorption of copper from aqueous solution. Parameters of importance that were investigated include initial pH, contact times, initial metal concentrations and adsorbent dosages. The result obtained indicates that pH of 6 and contact times of 3 hours were found to be optimum for the removal of copper. MISCBA demonstrates highest removal capacity of 38.84 mg/g as compared to raw sugarcane bagasse having capacity of 9.73 mg/g. The experimental data fits well into Freundlich and Langmuir isotherm models. Freundlich correlation coefficients were found to be 0.974 and 0.6512, whereas Langmuir correlation coefficients were 0.9181 and 0.9785, for both MISCBA and raw sugarcane bagasse respectively. Â© Research India Publications.